O cordel na BNCC: uma proposta de leitura literária - Sousa, André Sarmento de (2024)
This dissertation seeks to analyze the O Alienista em Cordel, written by Medeiros Braga, based on rewriting and its reading possibilities as a form of mediation between the text and the reader, aiming the literary reader development as recommended by BNCC. The hypothesis outlined in the construction of this research is based on the assumption that the teaching of literature is based on paradigms that causes estrangement from the reader to a literary text, distancing them from the reading experience and consequently erasing the subjective marks that are necessary for the reader's involvement in the process of fruition. By problematizing the distance between the reader's world and reading, we can reflect on the reality of teaching literature in high schools in Brazil, rethinking classroom practices, thus adopting the dynamics of literary literacy. We directed the methodological process towards bibliographical research, theoretically supported by the perspectives of Freire (1989), Langlade and Rouxel (2013), Colomer (2007), Larrosa (2022), Abreu (1999), Marinho and Pinheiro (2012), Adam and Heidman (2011), Cosson (2020;2021), Todorov (2020), among others. In order to achieve the objectives proposed in this research, we raised discussions about i) subjective reading as a process of constituting experience and fruition, considering the historical course of reading education in Brazil and its implications for the teaching of literature, ii) the different resources of fictional (re)creation of the cordel O Alienista, by Medeiros Braga, which can help the production of meanings by readers and consequently reaching the literary reader formation, iii) the dynamics of literary literacy and its methodological possibilities, proposing a lively dialogue between the literary text and the reader's experience, exploring the diversity of the cordel language such as: woodcuts, dramatization, theatrical games, songs, among others in a delightful environment in which the reader can get involved.